THE EFFECT OF WATCH THINK TALK STRATEGY ON STUDENTS’ SPEAKING ACHIEVEMENT - Irpan Azhari; Masitowarni Siregar (Universitas Negeri Medan, 2017)
This study deals with the effect of watch think talk strategy on students’ speaking achievement. The objective of this study is to find out whether the watch think talk strategy significantly affects students achievement in speaking. It was an experimental research. The subject of the study was students of the grade XI of MAN 1 Medan. The sample was divided into two groups. The experimental group was taught by applying Watch Think Talk Strategy, while the control group was taught by applying conventional strategy. The instrument for collecting the data was interview test. The data were analyzed by using t-test formula. The analysis showed that t-observed value 8.5 > t-table value 1.9 at α = 0.05 with dF= 78 the findings indicate that applying watch think talk strategy significantly affected students’ speaking achievement. Therefore, the null hyphothesis (Ho) is rejected and the hypothesis alternative (Ha) is accepted.